PENGARUH LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI MTs NEGERI 2 PONTIANAK - Oly Serviati; F. Y. Khosmas; Hadi Wiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine how much the effects of school environment have a relationship on students learning motivation on 8 th J students in MTs N 2 Pontianak. The method is a quantitative approach by using descriptive analysis (correlation study). Research population and sample was the 8 th J students in class. Therefore, the instrument of data collection was using questionnaire. According to the results of data analysis it showed that: 1) School environment consists of 3 aspects they are teachers, physicals environment and social environment with few of indicators in each of the aspects. Therefore, the school environment in MTs N 2 Pontianak in the middle level with amounts of 25 by the percentage 67%. 2) Learning motivation consists of 2 aspects they are intrinsic and extrinsic motivation with few of indicators in each of the aspects. Therefore, students’ learning motivation in 8th J class is in the middle level by the percentage 67%. 3) Based on the data analysis the coefficient of determination (R2) is 0,833 means 83, 3%. Adjusted R Square 0,685 means that school environment gave significant effects on students’ learning motivation by the percentage 68, 5%, while the remaining 31, 5% affected by the other factors.Keywords: School environment, Learning motivation, Social Science subject (IPS)